2019
DOI: 10.1038/s41467-019-11550-w
|View full text |Cite
|
Sign up to set email alerts
|

The prion-like protein kinase Sky1 is required for efficient stress granule disassembly

Abstract: Stress granules are membraneless protein- and mRNA-rich organelles that form in response to perturbations in environmental conditions. Stress granule formation is reversible, and persistent stress granules have been implicated in a variety of neurodegenerative disorders, including amyotrophic lateral sclerosis. However, characterization of the factors involved in dissolving stress granules is incomplete. Many stress granule proteins contain prion-like domains (PrLDs), some of which have been linked to stress g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 68 publications
4
40
0
Order By: Relevance
“…We recently identified Sky1 as a stress granule component and regulator of stress granule dynamics (8). However, while the Sky1 PrLD is sufficient for stress granule recruitment, deletion of the PrLD diminishes, but does not prevent, recruitment, highlighting a role for regions outside the PrLD (8). Like Sky1, some other full-length proteins containing assembly-prone PrLDs from our screen appear to localize to stress granules (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…We recently identified Sky1 as a stress granule component and regulator of stress granule dynamics (8). However, while the Sky1 PrLD is sufficient for stress granule recruitment, deletion of the PrLD diminishes, but does not prevent, recruitment, highlighting a role for regions outside the PrLD (8). Like Sky1, some other full-length proteins containing assembly-prone PrLDs from our screen appear to localize to stress granules (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 79%
“…PrLDs Form Reversible Assemblies upon Heat Shock. We recently showed that the PrLDs of Sky1, Cdc39, and Ded1 are sufficient for recruitment to stress granules upon heat stress (8). To determine how common this feature is among PrLDs, and to gain a greater understanding of how PrLDs might promote stress granule recruitment, we investigated the behavior of other isolated PrLDs in response to stress.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include for example components of mTORC1 complex, JNK and its scaffold protein WDR62, the ubiquitin peptidase USP10, the protein arginine methyltransferase (PRMT) 1 and PRMT5, the glycosyltransferase OGG1, and the poly-ADP-ribose polymerase PARP12 [70,408]. Accordingly, proteins within SGs were found to carry a plethora of posttranslational modifications including phosphorylation [250,409], GlcNac glycosylation [408], sumoylation [410], neddylation [411], ubiquitination [380], and ADP-ribosylation [264].…”
Section: Sgs As Signaling Hubs To Coordinate the General Stress Responsementioning
confidence: 99%